Investigation with using thermal analysis of gas evolution and sinteringof nanopowders of zirconia prepared by sol-gel method; Вестник Карагандинского университета. Серия Физика; № 1 (97) - Sheveleva E. A. Elena Aleksandrovna; Shevelev S. A. Sergey Anatolievich; Sokolovsky A. N. Aleksey Nikolaevich; Zeinidenov A. K. (2020, 2020)
Thermal and XRD analyses were used to study partially stabilized zirconia powders produced by sol-gel method in order to investigate gas evolution in annealing in air and densification behavior of these powders in compaction and subsequent sintering. It was found that the powders of the initial gel contain a large amount of gas adsorbates. The amount of adsorbates decreases as the annealing temperature grows. At annealing temperature of 700 ?C, adsorbates are completely removed from the powders and the latter obtain a crystalline structure with a predominant tetragonal phase. Gas adsorbates affect densification of powder compacts during sintering and facilitate the production of ceramics with a porosity of not more than 5 %. It is shown that the production of low porosity ceramics is complicated even though powders subjected to annealing may contain nano-sized impurities or be free of these. Low-melting additives are proposed to be used for ceramics production.